2018
DOI: 10.1093/biolre/ioy042
|View full text |Cite
|
Sign up to set email alerts
|

Human trophoblast epithelial-mesenchymal transition in abnormally invasive placenta†

Abstract: Differentiation of first trimester human placental cytotrophoblast (CTB) from an anchorage-dependent epithelial phenotype into the mesenchymal-like invasive extravillous trophoblast (EVT) is crucial in the development of the maternal-fetal interface. We showed previously that differentiation of first trimester CTB to EVT involves an epithelial-mesenchymal transition (EMT). Here we compare the epithelial-mesenchymal characteristics of CTB and EVT derived from normal third trimester placenta or placenta previa v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 38 publications
3
51
0
Order By: Relevance
“…Similar characteristics are found in cancer cells, and may result from similar molecular circuits involved in EMT and tumour development, which have been suggested to be regulated by epigenetic factors [22,45,46]. Previous data has shown that first trimester placental lysates and cytotrophoblasts are hypomethylated in gene blocks more closely related to cancer phenotypes (some of which were enriched for EMT) compared to third trimester samples [47]. Corresponding gene expression differences in EMT pathways in first versus third trimester placentae have also been reported, and together this data likely represents key gestational differences in placentation, as the majority of EVT differentiation and invasion occurs in the first half of pregnancy [22].…”
Section: Discussionmentioning
confidence: 64%
“…Similar characteristics are found in cancer cells, and may result from similar molecular circuits involved in EMT and tumour development, which have been suggested to be regulated by epigenetic factors [22,45,46]. Previous data has shown that first trimester placental lysates and cytotrophoblasts are hypomethylated in gene blocks more closely related to cancer phenotypes (some of which were enriched for EMT) compared to third trimester samples [47]. Corresponding gene expression differences in EMT pathways in first versus third trimester placentae have also been reported, and together this data likely represents key gestational differences in placentation, as the majority of EVT differentiation and invasion occurs in the first half of pregnancy [22].…”
Section: Discussionmentioning
confidence: 64%
“…A major pathway that causes EVT invasion is epithelial to mesenchymal transition (EMT) [57] which is known to be regulated by NFκB [58,59]. During EMT, cells change their shape, adhesion molecules, and polarity to become invasive and drive cell migration [55].…”
Section: Evt Function and Nfκb Actions In Normal Pregnancymentioning
confidence: 99%
“…Other ECM components, such as decorin and biglycan, were reported to be involved in placental invasion (20). In addition, ECM elasticity may direct cellular differentiation, including the epithelial-mesenchymal transition (EMT), and studies have indicated that trophoblast EMT has an important role in AIP (21,22). MMPs in the ECM are able remodel the ECM to facilitate EMT, promoting cell specification during embryonic and placental development (23,24).…”
Section: Discussionmentioning
confidence: 99%